Seizure-Associated Brain Injury in Perinatal Asphyxia - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2002)
Brain injury in term infants with neonatal asphyxia and seizures was evaluated by MRI and MRS at the University of California, San Francisco.